Predation landscapes influence migratory prey ecology and evolution. (August 2021) - Sabal, Megan C.; Boyce, Mark S.; Charpentier, Corie L.; Furey, Nathan B.; Luhring, Thomas M.; Martin, Hans W.; Melnychuk, Michael C.; Srygley, Robert B.; Wagner, C. Michael; Wirsing, Aaron J.; Ydenberg, Ronald C.; Palkovacs, Eric P.
Abstract : Migratory prey experience spatially variable predation across their life cycle. They face unique challenges in navigating this predation landscape, which affects their perception of risk, antipredator responses, and resulting mortality. Variable and unfamiliar predator cues during migration can limit accurate perception of risk and migrants often rely on social information and learning to compensate. The energetic demands of migration constrain antipredator responses, often through context-dependent patterns. While migration can increase mortality, migrants employ diverse strategies to balance risks and rewards, including life history and antipredator responses. Humans interact frequently with migratory prey across space and alter both mortality risk and antipredator responses, which can scale up to affect migratory populations and should be considered in conservation and management. Highlights: Predation shapes migration with diverse ecological and evolutionary effects throughout the predation process, including the perception of predator cues, antipredator responses, and mortality. Migrants use social information and learning to overcome the challenge of variable and unfamiliar predator cues across the migratory landscape. The energetic demands of migration can constrain antipredator responses; however, constraints are often context-dependent and do not prevent some migrants from exhibiting large and effective responses. Migration makes prey vulnerable to predators, but migrants employ diverse strategies to balance risks and rewards, including life history and antipredator responses. Humans can indirectly harm migratory populations by altering predation landscapes, which should be considered in conservation and management plans.